Energy level alignment at zinc blende Cd(Mn)Se/ZnTe/InAs(100) interfaces - Gleim, Thomas; Weinhardt, L.; Schmidt, Th.; Fink, Rainer; Heske, C.; Umbach, E.; Grabs, P.; Schmidt, G.; Molenkamp, L.W.; Richter, B.; Fleszar, A.; Steinrück, Hans-Peter (Applied Physics Letters, 2002)
Experimentally determined band offsets of the CdSe/ZnTe/InAs(100) semiconductor heterostructures were presented. The semimagnetic system showed to behave very similar to the Mn-free model system. A stepwise alignment of the valence bands and in the ZnTe interlayer a 1.1 eV conduction band tunnel barrier were found.